Evaluation of the Effect of Sociocultural Factors on the Children Stature in Langkat Regency, Indonesia - Nasution, Siti Saidah; Girsang, Bina Melvia; Hariati, Hariati (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Stunting is a chronic malnutrition due to insufficient nutrition for a long period of time. This condition results the child to not having a proper body height in his age and raises risks for short and long term. North Sumatra, Indonesia, is one area with frequent number of stunting incidences, especially in the regency of Langkat. Socioculture is one of the factors that are closely related to stunting since it is related to the care method of infants and children, including the fulfillment of food and family nutrition. Therefore, failing to provide these supports will cause stunting to emerge. AIM: This study was aimed to investigate the relationship between sociocultural factors and babies and toddler with stunting, particularly in Langkat Regency, Indonesia. METHODS: This study is a descriptive correlation using survey to determine the sociocultural relationship of the community to the incidence of stunting in Langkat district, especially the Secanggang subdistrict. Using total sampling method, 136 family/parents that have babies/children were chosen. Data were collected through questionnaires, which consisted of demographic data, sociocultural data, and health status. Furthermore, data analysis was performed using Chi-square statistical test, while multivariate test analysis was conducted through logistic regression. RESULTS: This research discovers and confirms that social-cultural factors have a significant effect as the cause of stunting. CONCLUSION: The sociocultural factors which were related to stunting are environmental sanitation, parents educational background, family income, and mother’s knowledge. Therefore, further and comprehensive study on sociocultural is needed to be performed to overcome stunting in community.